Alkali Metal Catalysed Double Hydrophosphorylation of Nitriles and Alkynes. Issue 16 (16th April 2019) - Banerjee, Indrani; Harinath, Adimulam; Panda, Tarun K.
Abstract : Catalytic C–P and N–P bond formation via double hydrophosphorylation of nitriles with diphenylphosphane oxide using alkali metal precatalyst [MN(SiMe3 )2 ] (M = Li, Na, K) is reported. The potassium congener was observed to be the most efficient catalyst for converting aryl nitriles to the corresponding N‐((diphenyl‐phosphoryl)(aryl)methyl)‐P, P‐diphenylphosphinic amide [ArCHP(O)‐Ph2 NHP(O)Ph2 ] at mild temperature (60 °C) and with neat reactants. Double hydrophosphorylation of alkynes with HP(O)Ph2 is also very effective when [KN(SiMe3 )2 ] is used as a precatalyst at room temperature and gives the corresponding 1, 2‐diylbis(diphenyl‐phosphane oxide [RCHP(O)Ph2 CH2 P(O)Ph2 ] as the product. A wider substrate scope of both reactions is explored. Abstract : Double hydrophosphorylation of nitriles and terminal alkynes with diphenylphosphane oxide with high yield and chemoselectivity for the preparation of organophosphorus compounds using alkali metal salts [MN(SiMe3 )2 ] (M = Li, Na, K) as precatalysts under ambient conditions is reported.